Implementasi Inverter Berbasis Square Wave dan Sinusoidal PWM Menggunakan Arduino Uno - R Dwiki Rachwanto; Saidah Saidah; Amirullah Amirullah (Rekayasa, 2022)
Inverters with square waves and sinusoidal output signal waves have different efficiency values. The difference is very visible, especially when the inverter is used to drive an electric device that uses a motor. In a sinusoidal wave type inverter, electricity consumption will be more efficient than the use of a square wave type inverter. This study aims to determine the efficiency value of the square wave and sinusoidal inverter wave output in supplying the load. Square wave and sinusoidal inverters require a controller, the controller uses an Arduino Uno which acts as an SPWM signal generator and a square wave signal is used to drive the MOSFET with push-pulls topology. Based on the results of the inverter test to determine the efficiency, it shows that the inverter with sinusoidal output is 96.40% better, while the inverter with square wave output is only 83.34%, this test is carried out using a 50W LED lamp load.